The influence of static and dynamic stretching on the performance of an elite volleyball hitter - Pegram, S. E. (Concordia University, Saint Paul, 2023)
The purpose of this study is to show the effects of static and dynamic stretching on elite volleyball performance and improvement. Being a volleyball player requires the use of the entire body. Range of motion and the lower extremities are used most in playing this sport, with injury being most frequent in those regions. These techniques are common in the sport and can show benefits for these troubled areas. Sixty-four collegiate Division III front-row volleyball players will participate and be randomly placed into four groups. These four groups will complete a 12-week warm-up and cool-down program, not knowing which group they would be in. The Control group will complete basic skills warm-up and cool-down sessions prior to their normal drills. The Static Stretching Group will complete five minutes of static stretching and ten minutes of a basic warm-up and cool-down. The Dynamic Stretching Group will perform five minutes of dynamic stretching and ten minutes of a basic warm-up and cooldown session. The Combined Stretching Group will complete five minutes of static and dynamic stretching and ten minutes of a basic warm-up and cool-down session. Measurements of flexibility will be completed with a goniometer and the strength of the lower extremities will be evaluated with a force plate. The results of this study can be beneficial to volleyball players and coaches because it can contribute to the creation of optimal warm-up sessions. It is hypothesized that the addition of static and dynamic stretching will contribute to an increase in flexibility and strength among athletes.